THE FORMATION AND HISTORICAL SIGNIFICANCE OF THE KOKAND KHANATE (International journal of artificial intelligence, 2025)
The Kokand Khanate, which emerged in the early 18th century in the Fergana Valley, played a crucial role in the political, cultural, and economic development of Central Asia. This article explores the historical background, formation process, and sociopolitical structure of the Kokand Khanate, as well as its contribution to regional identity and statehood. The study highlights how the khanate evolved from a small local principality into a powerful state under the rule of leaders such as Shahrukhbek, Narbuta Khan, and Umar Khan. It also examines the Khanate’s administrative system, trade relations, and its influence on Islamic education and culture. Furthermore, the article discusses the causes of its decline in the late 19th century and its eventual annexation by the Russian Empire in 1876. The Kokand Khanate remains a symbol of national awakening and resilience, representing a significant stage in the historical development of Uzbekistan and the broader Turkic world.